2005
DOI: 10.1177/1087057105276318
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a High-Throughput Screening Assay for HIV-1 Integrase Enzyme Activities

Abstract: Integrase (IN) mediates the covalent insertion of the retroviral genome into its host chromosomal DNA. This enzymatic activity can be reconstituted in vitro with short DNA oligonucleotides, which mimic a single viral DNA end, and purified IN. Herein we report a highly efficient and sensitive high-throughput screen, HIV Integrase Target SRI Assay (HITS™), for HIV-1 IN activity using 5′ biotin-labeled DNA (5′ BIO donor) and 3′ digoxygenin-labeled DNA (3′ DIG target). Following 3′ processing of the 5′ BIO donor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…Therefore, identification and development of new HIV-1 inhibitor is still an urgent task for anti-HIV-1 drug research nowadays. Diverse screening strategies were used for the discovery of new HIV-1 agents [20][21][22][23]. Cell-based screening assay offer some advantages in the quest for novel inhibitors because it allows for the screening of multiple targets simultaneously, even in some cases revealing targets not captured in biochemical assays.…”
Section: Hiv-1 High-throughput Screening Inhibitor Virus-cell-basementioning
confidence: 99%
“…Therefore, identification and development of new HIV-1 inhibitor is still an urgent task for anti-HIV-1 drug research nowadays. Diverse screening strategies were used for the discovery of new HIV-1 agents [20][21][22][23]. Cell-based screening assay offer some advantages in the quest for novel inhibitors because it allows for the screening of multiple targets simultaneously, even in some cases revealing targets not captured in biochemical assays.…”
Section: Hiv-1 High-throughput Screening Inhibitor Virus-cell-basementioning
confidence: 99%
“…, a donor oligonucleotide that mimics 1 of the viral DNA ends, and a target oligonucleotide [11][12][13][14][15][16][17][18][19][20] . Traditionally, IN activity is measured by a radiolabeled substrate assay in which reaction products are separated on polyacrylamide denaturing gels and subjected to autoradiography [1,11,12] .…”
Section: +mentioning
confidence: 99%
“…However, the disadvantages of the method are that: (i) it requires radiolabeled substrates, special equipment, and appropriate handling of hazardous radioactive waste; and (ii) it is inconvenient to process a large amount of reactions due to the lowthroughput format. Compared with the radiolabeled substrate assay, biotin (or digoxin)-labeled microtiter plate assays are safe and high-throughput, and the products of IN reactions are easy to measure with a spectrophotometer [14][15][16] . However, the major drawbacks of these microtiter plate assays are the low signal/noise ratio and intensive labor because of the necessity for plate coating and repeated washing.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction is then initiated by the addition of target dsDNA labelled in some manner, and after an incubation period, the ligated product is quantified. John et al (2005) reported a highly efficient and sensitive high-throughput screen, HIV IN Target SRI Assay for HIV-1 IN activity, using 5' biotin-labelled DNA (5' BIO donor) and 3' digoxygenin-labelled DNA (3' DIG target). Following 3' processing of the 5' BIO donor, strand transfer proceeds with integration of the 5' BIO donor into the 3' DIG target.…”
Section: Hiv-1 Enzyme Targetsmentioning
confidence: 99%